The bombing of Auschwitz : should the Allies have attempted it? - Neufeld, Michael J., 1951- 1951- (St. Martin's Press [u.a.], 2000)
A series of essays on questions surrounding a proposed Allied bombing campaign on Auschwitz in 1944.